MySQL - DuBois, Paul 1956- (Addison-Wesley, 2009)
The Definitive Guide to Using, Programming, and Administering MySQL 5.0 and 5.1 MySQL is an open source relational database management system that has experienced a phenomenal growth in popularity and use. Known for its speed and ease of use, MySQL has proven itself to be particularly well-suited for developing database-backed websites and applications. In MySQL, Paul DuBois provides a comprehensive guide to using and administering MySQL effectively and productively. He describes everything from the basics of getting information into a database and formulating queries, to using MySQL with PHP or Perl to generate dynamic web pages, to writing your own programs that access MySQL databases, to administering MySQL servers. The fourth edition of this bestselling book has been meticulously revised and updated to thoroughly cover the latest features and capabilities of MySQL 5.0, as well as to add new coverage of features introduced with MySQL 5.1. "One of the best technical books I have read on any subject."--Gregory Haley, C Vu, The Association of C & C++ Users "A top-notch user's guide and reference manual, and in my opinion, the only book you'll need for the daily operation and maintenance of MySQL databases."--Eugene Kim, Web Techniques Introduction 1 Part I: General MySQL Use Chapter 1: Getting Started with MySQL 13 Chapter 2: Using SQL to Manage Data 101 Chapter 3: Data Types 201 Chapter 4: Stored Programs 289 Chapter 5: Query Optimization 303 Part II: Using MySQL Programming Interfaces Chapter 6: Introduction to MySQL Programming 341 Chapter 7: Writing MySQL Programs Using C 359 Chapter 8: Writing MySQL Programs Using Perl DBI 435 Chapter 9: Writing MySQL Programs Using PHP 527 Part III: MySQL Administration Chapter 10: Introduction to MySQL Administration 579 Chapter 11: The MySQL Data Directory 585 Chapter 12: General MySQL Administration 609 Chapter 13: Access Control and Security 699 Chapter 14: Database Maintenance, Backups, and Replication 737 Part IV: Appendixes Appendix A: Obtaining and Installing Software 777 Appendix B: Data Type Reference 797 Appendix C: Operator and Function Reference 813 Appendix D: System, Status, and User Variable Reference 889 Appendix E: SQL Syntax Reference 937 Appendix F: MySQL Program Reference 1037 Note: Appendixes G, H, and I are located online and are accessible either by registering this book at informit.com/register or by visiting www.kitebird.com/mysql-book . Appendix G: C API Reference 1121 Appendi ...
Print version record
Keywords: MySQL (Electronic resource); SQL (Computer program language); Database management; SQL (Langage de programmation); Bases de données; Gestion